Clinical management of a fused mandibular lateral incisor with supernumerary tooth: A case report - Seda Aydemir; Emre Ozel; Goze Arukaslan; Neslihan Tekce (Wolters Kluwer Medknow Publications, 2016)
The purpose of this report is to present a rare case of a fused mandibular lateral incisor with supernumerary tooth with a follow-up for 18-months. A 35-year-old female patient was referred to our clinic with an extraoral sinus tract in the chin. The intraoral diagnosis revealed the fusion of her mandibular lateral incisors. Vitality pulp tests were negative for mandibular right central and lateral incisors. Radiographic examinations showed a fused tooth with two separate pulp chambers, two distinct roots, and two separate root canals. There were also periapical lesion of fused teeth and mandibular right central incisor, so endodontic treatment was carried out the related teeth. Radiographic examination revealed a complete healing of the lesion postoperatively at the end of 18-months. This paper reports the successful endodontic and restorative treatment of unilateral fused incisors. Because of the abnormal morphology of the crown and the complexity of the root canal system in fused teeth, treatment protocols require special attention.